2020
DOI: 10.1038/s41598-020-59508-z
|View full text |Cite
|
Sign up to set email alerts
|

Light transport and vortex-supported wave-guiding in micro-structured optical fibres

Abstract: In hydrodynamics, vortex generation upon the transition from smooth laminar flows to turbulence is generally accompanied by increased dissipation. However, plane vortices can provide transport barriers and decrease losses, as it happens in numerous geophysical, astrophysical flows and in tokamaks. Photon interactions with matter can affectlight transportin waveguides in unexpected and somewhat counterintuitive ways resembling fluid dynamics. Here, we demonstrate dramatic impact of light vortex formation in mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 47 publications
1
16
0
2
Order By: Relevance
“…Additionally, the vortex-like dynamics of the radial component of the Poynting vector contour lines inside the fibre structure are remarkable. This interesting behaviour, also observed in other works 25 , 26 , calls for further exploration of the transverse energy flow in HCPCFs.…”
Section: Resultssupporting
confidence: 80%
“…Additionally, the vortex-like dynamics of the radial component of the Poynting vector contour lines inside the fibre structure are remarkable. This interesting behaviour, also observed in other works 25 , 26 , calls for further exploration of the transverse energy flow in HCPCFs.…”
Section: Resultssupporting
confidence: 80%
“…Both phase distributions (Figure 3) are governed by a nonlinear rule [16] and these vortices are called anisotropic. In our work [17], we showed that the coordinates of the vortex centers of the transverse component of the Poynting vector of the leaky core modes also satisfy the equation P x (x, y) = P y (x, y) = 0, where P x and P y are projections of the transverse component of the Poynting vector.…”
Section: Role Of Losses In Vortex Formation In Hollow Core Waveguidesmentioning
confidence: 84%
“…Both phase distributions (Figure 3) are governed by a nonlinear rule [16] and these vortices are called anisotropic. In our work [17], we showed that the coordinates of the vortex centers…”
mentioning
confidence: 84%
“…A significant step forward in reducing the confinement loss was obtained with the introduction of the hypocycloid core contour (also known as negative curvature) by Benabid and co-workers [16], since it has effect both on spatial overlap and on frequency mismatch [6,17]. Other approaches based on light vortex have been proposed to explain the beneficial effects of the hypocycloidal core shap [18]. As of today, many hypocycloidal HC-ICF designs have been proposed and experimentally demonstrated, having loss not only lower than HC-PBGFs but also lower than solid-core silica fibers, both at short wavelengths [19,20], where losses are bound by Rayleigh scattering, and at long wavelengths [3,21,22], where they are bound by material absorption.…”
Section: Introductionmentioning
confidence: 99%